Multi-layer protruded electrodes for reducing the operating voltage and gamma shift of fringe-field switching LCDs. Issue 4 (15th March 2020) - Guo, Yuqiang; Li, Xiaoshuai; Li, Wenjuan; Huai, He; Zhang, Hui; Ma, Hongmei; Sun, Yubao
ABSTRACT: To reduce the operating voltage and gamma shift of the nematic liquid crystal display (LCD), a single-domain-protruded fringe-field switching (PFFS) electrode structure is designed. In this work, a kind of nematic liquid crystal (NLC) is introduced firstly. Then, the operating voltage and gamma shift of the proposed PFFS LCD are investigated under various electrodes' parameters. Besides, its light leakage and contrast ratio are also discussed. The results show that the operating voltage of the PFFS LCD is only 1.40 V, here the electrodes' width is 2 μm and electrodes' gap is 4 μm. The gamma shift of the PFFS LCD can be reduced to the indistinguishable level under various electrodes' sizes, if the height of the insulation layer is proper. For contrast ratio, it is larger than 200:1 at full viewing-angle, and the zone of 500:1 covers 60° polar angle. Graphical abstract: